Host-guest interactions between first-generation immigrants and their visiting relatives: social exchange, relations of care and travel. Issue 3 (7th August 2017) - Capistrano, Robert Charles; Weaver, Adam
Abstract : Purpose: This paper aims to examine the social interactions between Filipino immigrant-hosts residing in New Zealand and their visiting relatives (VRs) or guests from the Philippines using social exchange theory to understand their experiences. Design/methodology/approach: This qualitative, multi-sited study used in-depth interviews to examine social interactions between Filipino immigrant-host families in New Zealand and their respective visiting relatives from the Philippines. Findings: Hosting VRs reflects aspects of social exchange theory, and the interdependence and familial obligations related to VR travel demonstrate mutual relations of care. Maintaining relations of care within the family is an ongoing process involving intergenerational relationships that bind together immigrant-host families and their VRs. Research limitations/implications: The conceptualization of the social interactions between immigrants-hosts and VRs is not generalizable owing to the small sample size and lack of representativeness. However, despite a small sample, this qualitative inquiry uncovered a series of personal meanings and understandings attached to the maintenance of familial bonds. Practical implications: As immigrant-receiving countries become more culturally diverse through migration, research about other cultures will assist tourism planners in understanding the values and actions of a more varied array of residents. A better understanding of travel experiences and interactions between immigrants and their guests may provide marketers with insights into host-guest dynamics within a VR context, thus potentially enabling tourism marketers to create better marketing campaigns. Social implications: Future studies may be undertaken from non-Western and Western perspectives that examine the social interactions between hosts and guests in the context of VR travel. Very little research has been conducted that addresses the meanings and understandings attached to these interactions from the perspectives of both hosting and visiting groups. This research highlights the importance of families in tourism, a contrast with the relative blindness of tourism scholarship toward relations of domesticity and sociality. Originality/value: What separates the social interactions between family members in the context of visiting friends and relatives travel from the traditional host-guest paradigm is that it does not involve strangers. This study uses social exchange theory to examine social interactions between hosts and guests who are familiar with each other.